Truth from the machine: artificial intelligence and the materialization of identity. (3rd April 2021) - Keyes, Os; Hitzig, Zoë; Blell, Mwenza
ABSTRACT: Critics now articulate their worries about the technologies, social practices and mythologies that comprise Artificial Intelligence (AI) in many domains. In this paper, we investigate the intersection of two domains of criticism: identity and scientific knowledge. On one hand, critics of AI in public policy emphasise its potential to discriminate on the basis of identity. On the other hand, critics of AI in scientific realms worry about how it may reorient or disorient research practices and the progression of scientific inquiry. We link the two sets of concerns—around identity and around knowledge—through a series of case studies. In our case studies, about autism and homosexuality, AI figures as part of scientific attempts to find, and fix, forms of identity. Our case studies are instructive: they show that when AI is deployed in scientific research about identity and personality, it can naturalise and reinforce biases. The identity-based and epistemic concerns about AI are not distinct. When AI is seen as a source of truth and scientific knowledge, it may lend public legitimacy to harmful ideas about identity.